2021
DOI: 10.3390/biology10020117
|View full text |Cite
|
Sign up to set email alerts
|

Osteoclasts Differentiation from Murine RAW 264.7 Cells Stimulated by RANKL: Timing and Behavior

Abstract: The development of multi-nucleated cells is critical for osteoclasts (OCs) maturation and function. Our objective was to extend knowledge on osteoclastogenesis, focusing on pre-OC fusion timing and behavior. RAW 264.7 cells, which is a murine monocyte-macrophage cell line, provide a valuable and widely used tool for in vitro studies on osteoclastogenesis mechanisms. Cells were treated with the receptor activator of nuclear factor κ-B ligand (RANKL) for 1–4 days and effects on cell morphology, cytoskeletal orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 34 publications
1
36
0
Order By: Relevance
“…The methods suggested by Lampiasi, Nadia et. al, 2021 [ 35 ] were applied in our study for osteoclasts differentiation from murine RAW264.7 cells stimulated by RANKL. Western blot analyses showed that compared with negative control (NC) or RAW264.7 cells co-cultured with miR-21 inhibitor-treated AFs, RAW264.7 cells co-cultured with miR-21 mimic pre-treated AFs showed upregulated expression of osteoclast differentiation markers, matrix metallopeptidase (MMP) 9, receptor activator of NFκB ligand (RANKL), triiodothyronine receptor auxiliary protein (TRAP), and osteoprotegerin (OPG) proteins ( Figure 3 B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The methods suggested by Lampiasi, Nadia et. al, 2021 [ 35 ] were applied in our study for osteoclasts differentiation from murine RAW264.7 cells stimulated by RANKL. Western blot analyses showed that compared with negative control (NC) or RAW264.7 cells co-cultured with miR-21 inhibitor-treated AFs, RAW264.7 cells co-cultured with miR-21 mimic pre-treated AFs showed upregulated expression of osteoclast differentiation markers, matrix metallopeptidase (MMP) 9, receptor activator of NFκB ligand (RANKL), triiodothyronine receptor auxiliary protein (TRAP), and osteoprotegerin (OPG) proteins ( Figure 3 B).…”
Section: Resultsmentioning
confidence: 99%
“…The method suggested by Lampiasi, Nadia et al, 2021 with little modification [ 35 ] was applied in our study for osteoclasts (OC) differentiation from murine RAW 264.7 cells. In the brief to induce OC differentiation, the murine cells were suspended in an alpha-minimal essential medium (α-MEM Gibco, Grand Island) with 10% heat-inactivated fetal bovine serum (FBS, Sigma-Aldrich, USA), 100-U/mL penicillin, and 100-µg/mL streptomycin; after 24 h of the cultivation period, the previous α-MEM media was replaced with serum-free-α-MEM medium supplemented with 50-ng/mL RANKL-Recombinant-Protein (ThermoFisher, RP-8601) and human M-CSF (20 ng/mL; ThermoFisher, RP-8615).…”
Section: Methodsmentioning
confidence: 99%
“…We have previously shown the timing and behavior of pre-OCs differentiation after RANKL stimulation of RAW264.7 cells over a 4-day period and at different levels, i.e., cell morphology, cytoskeletal organization, protein distribution, signaling pathways role, and OC-specific gene expression [ 4 , 5 , 29 ]. In particular, based on our previous studies on the expression of NFATc1 showing that both mRNA and protein levels increased already on the first day of RANKL stimulation, we established that this was the best RANKL stimulation time to perform miRNA expression analyses.…”
Section: Resultsmentioning
confidence: 99%
“…Focal adhesion (04510, within “cellular processes”) and ECM–receptor interaction (04512, within “signal transduction”) are pathways that seem very interesting to analyze, partly because we have recently evaluated the differentiation of OCs on different substrates [ 5 ]. Focal adhesion pathway was significantly associated with miRNAs belonging to all the groups ( Table 3 ), while ECM–receptor interaction was associated only with miRNAs of the group 3 ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation